Analisis Citra Merek, Kualitas Produk, Serta Harga Dalam Mempengaruhi Keputusan Pembelian Konsumen Produk Laptop Lenovo - Syafrianda, Adityan; Kusuma, Kumara Adji; Indayani, Lilik (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to analyze brand image, product quality and price on purchasing decisions of Lenovo laptop product users. This study uses a quantitative approach. The population in this research is all Sidoarjo people who use Lenovo laptop products. The sampling technique for this research was carried out using a probability sampling method with a random sampling technique with a total of 100 respondents. The data collection technique is by distributing questionnaires to the Sidoarjo community using interval measurements and answers are measured using a Likert scale. The data analysis technique in this research uses the SmartPLS (Smart Partial Least Square) application. The results of this research show that brand image, product quality and price have a significant influence on purchasing decisions for Lenovo laptop products in the Sidoarjo community.